Lust, caution - Kong, William; Lee, Ang (Universal City, CA : Universal Studios Home Entertainment, 2007)
Set against the backdrop of Japanese occupied Shanghai in 1942, a young woman finds herself swept up in a radical plot to assassinate a ruthless and secretive intelligence agent. As she immerses herself in her role as a cosmopolitan seductress, she becomes entangled in a dangerous game of emotional intrigue, love and betrayal
Based on the story by Eileen Chang
Title from title screen
Director of photography, Rodrigo Prieto ; editor, Tim Squyres ; music, Alexandre Desplat ; costume designer, Lai Pan ; production designer, Lai Pan
Cast: Tony Leung Chiu Wai, Wei Tang, Joan Chen, Lee-Hom Wang, Chung Hua Tou
DVD Format
Dolby digital 5.1 surround.
Keywords: Man-woman relationships -- Drama; Assassination -- China -- Drama; Femmes fatales -- China -- Drama